2021
DOI: 10.1007/s12098-021-03894-3
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 in Children with Cancer and Continuation of Cancer-Directed Therapy During the Infection

Abstract: Objective To report the experience with COVID-19 in children with cancer at the largest tertiary-cancer care and referral center in India. Methods This study is a single tertiary center experience on COVID-19 in children with cancer and continuation of cancer-directed therapy in them. Children ≤ 15 y on active cancer treatment detected with COVID-19 until September 15 th , 2020 were prospectively followed up in the study. Patients were managed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 17 publications
1
16
0
Order By: Relevance
“…It is pertinent to note that, although majority of children (94.2%) had only mild disease, COVID-19-related mortality in this cohort was 4.9%, which is relatively higher than that observed in children in general [3]. This reiterates the need for adopting newer strategies to limit the infection in this vulnerable cohort of children.…”
mentioning
confidence: 67%
See 3 more Smart Citations
“…It is pertinent to note that, although majority of children (94.2%) had only mild disease, COVID-19-related mortality in this cohort was 4.9%, which is relatively higher than that observed in children in general [3]. This reiterates the need for adopting newer strategies to limit the infection in this vulnerable cohort of children.…”
mentioning
confidence: 67%
“…Yet, systematic studies of impact of COVID-19 infection and treatment disruptions on cancer care of children are few, especially in resource-constrained settings. In this issue of the Journal, the study by Parambil et al provides an important snapshot of experience of managing COVID-19 infection among children with cancer along with strategies for treatment adaptations [3].…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…In contrast to these findings, a Turkish investigation reported on a dramatic decrease in the number of both de novo diagnosed and treated pediatric cancer patients [ 18 ]. Participants of the St Jude Global Alliance and International Society for Paediatric Oncology survey also reported on a reduction of newly diagnosed patients and gross interruptions, even complete abandonment of anticancer therapies delivered [ 19 21 ]. According to this group of investigators, severe and critical conditions of COVID-19 were observed in one fifth of patients and deaths occurred in a higher proportion than were reported in the literature surveying the general pediatric population.…”
Section: Discussionmentioning
confidence: 99%